Liquidity measures, liquidity drivers and expected returns on an early call auction market - Carsten Burhop; Sergey Gelman (Max Planck Institute for Research on Collective Goods, 2011)
We analyze the determinants of illiquidity and its impact on asset pricing for purely call-auction traded stocks on Berlin Stock Exchange using 22 years of daily data (1892-1913). We use the Lesmond et al. (1999) measure of transaction costs to proxy illiquidity. We show that transaction costs were low and comparable to today's costs. Liquidity was negatively correlated with active informed trading, particularly being low for small and distressed stocks and in crises times. Liquidity concerns were a major driver of asset pricing: we find significant illiquidity level and illiquidity risk premia as well as an explicit premium for informed trading.
Keywords: N23; G12; G14; 330; Transaction Costs; Liquidity Premium; Informed Trading; Börsenkurs; Marktliquidität; Risikoprämie; Insiderhandel; Geschichte; Deutschland (bis 1945)